Implementation of Green Innovation Strategy in UMKM in Muara Penimbung Village - Maryati, Sri; Sartika Pratiwi, Trie; Paramita Gobel, Alieftyani; Pebryan Jaya, Eko (Unram Journal of Community Service, 2025)
Small, Micro and Medium Enterprises are currently receiving more attention from the government, as reflected in the downstream program which until now is still the main focus of the government. MSMEs play an important role in the Indonesian economy. It is important for MSMEs to continue to grow and survive by implementing renewable strategies. Green Innovation is a qualified strategic choice at this time in line with the increasing public awareness of environmental sustainability through the implementation of green product innovations and green process innovations. Muara Penimbung Village which is a village that is familiar with songket craftsmen. The diversity of educational backgrounds and people's livelihoods is one of the factors that makes songket MSMEs in Muara Penimbung Village need understanding and knowledge related to green innovation for the sustainability of their business. Based on the results and discussions of the service that has been carried out, it can be concluded that green innovation specially process innovation and green products, is an innovation needed by Songket MSMEs, with a more environmentally friendly process and products produced by combining safer materials by paying attention to consumer health provides value for Songket MSME owners.